IL-10-Producing B Cells Suppress Effector T Cells Activation and Promote Regulatory T Cells in Crystalline Silica-Induced Inflammatory Response In Vitro - Yiping Lu; Fangwei Liu; Chao Li; Ying Chen; Dong Weng; Jie Chen (Mediators of Inflammation)
Long-term exposure to crystalline silica leads to silicosis, which is characterized by persistent lung inflammation and lung fibrosis. Multiple immune cells have been demonstrated to participate in crystalline silica-induced immune responses. Our previous study indicated that B10 could control lung inflammation through modulating the Th balance in experimental silicosis in mice. However, the regulatory mechanism of B10 on CD4+ T cells is still unclear. MACS-sorted CD19+ B cells from the three different groups were cultured with CD4+ T cells either with or without transwell insert plates to evaluate the effects of B10 on CD4+ T cells, including Teff and Treg. B10 was eliminated by anti-CD22 application in vivo. Flow cytometry was used to test the frequencies of CD4+ T cells, and the expressions of the related cytokines were detected by real-time PCR and CBA. Insufficient B10 elevated the levels of proinflammatory cytokines and promoted Th responses in a way independent upon cell-cell contact in the Teff and B cell coculture system. B10 could both increase Treg activity and enhance conversion of Teff into Treg. Our findings demonstrated that B10 could affect Th responses by the release of IL-10, enhancing Treg functions and converting Teff into Treg.